Analisis Pengendalian Persediaan Bahan Baku menggunakan Metode Material Requirement Planning (MRP) untuk meningkatkan Efisiensi Operasional Pada Ojii Coffe And Eatery di Surakarta - Elisa Tri Hapsari; Arlia Sherlyna; Deninta Dwiana Kurniasih; Desi Nathazari (CV. Aksara Global Akademia, 2026)
. Raw material inventory management plays an important role in maintaining operational continuity and cost efficiency in the food anf beverage industry. Ojii Coffe and Eatery in solo manages its coffe bean inventory based on estimated demand, resulting in excess inventory and additional holding costs. This study aims to analyze raw material inventory control using the Material Requirement Planning (MRP) method to improve operational efficiency. A quantitative case study approach was employed using purchasing, production, and raw material usage data for coffee beans in 2025. Inventory planning was analyzed using the MRP method with the Lot For Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ) techniques. The results indicate that the company's existing inventory policy generated a total inventory cost of Rp780,000, while the LFL, EOQ, and POQ techniques resulted in inventory costs of Rp300,000, Rp905,000, and Rp300,000, respectively. The LFL and POQ techniques produced the lowest inventory costs, demonstrating greater efficiency than the company's existing inventory policy and the EOQ technique. These findings suggest that implementing MRP, particularly the LFL and POQ techniques, can improve inventory planning and reduce inventory costs in coffee shop operations